Endolymphatic Hydrops Magnetic Resonance Imaging in Menire's Disease Patients on a Vertigo Attack. Issue 4 (17th April 2022) - Chen, Wei; Geng, Yue; Niu, Yue; Lin, Mengyan; Lin, Naier; Sha, Yan
Abstract : Objective: To investigate the characteristics of endolymphatic hydrops (EH) in Menire's disease (MD) patient on a vertigo attack. Study Design: Prospective study. Setting: Tertiary referral center. Patients: Thirty-six MD patients underwent the enhanced magnetic resonance imaging (MRI) examinations of the inner ear on a vertigo attack were enrolled. Main Outcome Measures: All patients met the diagnostic criteria for MD and underwent intravenous gadolinium injection 4 hours before the MRI examinations. The MRI examinations were performed in MD patients on a vertigo attack. Results: Various degrees of vestibular EH appeared in almost all affected ears (2 ears had no EH, 11 ears had mild EH, 26 ears had significant EH). The positive rate of vestibular EH was 37/39 (94.9%). Cochlear EH occurred in 29 ears among 39 affected ears (17 ears had mild EH, 12 ears had significant EH). Conclusion: MRI with intravenous gadolinium injection can provide a better assessment of EH in MD patient on a vertigo attack. Vestibular EH seems to be closely related with the vertigo attacks in MD patients, which needs further study.